Assessing second cancer risk after primary cancer treatment with photon or proton radiotherapy. Issue 15 (19th May 2020) - DeLaney, Thomas F.; Yock, Torunn I.; Paganetti, Harald
Abstract : In this issue, Xiang and colleagues present data from the National Cancer Database comparing the number of second malignancies observed in adult and pediatric patients with 9 major cancer subtypes who received different radiation modalities. These are important findings because understanding the risk of late, radiation‐associated malignancies with different radiation modalities may help physicians reduce the risk of this devastating late treatment effect.